Collaboration behind-the-scenes: key to effective interprofessional education. Issue 4 (July 2014) - MacKenzie, Diane E.; Doucet, Shelley; Nasser, Susan; Godden-Webster, Anne L.; Andrews, Cynthia; Kephart, George
Abstract A variety of stakeholders, including students, faculty, educational institutions and the broader health care and social service communities, work behind-the-scenes to support interprofessional education initiatives. While program designers are faced with multiple challenges associated with implementing and sustaining such programs, little has been written about how program designers practice the interprofessional competencies that are expected of students. This brief report describes the backstage collaboration underpinning the Dalhousie Health Mentors Program, a large and complex pre-licensure interprofessional experience connecting student teams with community volunteer mentors who have chronic conditions to learn about interprofessional collaboration and patient/client-centered care. Based on our experiences, we suggest that just as students are required to reflect on collaborative processes, interprofessional program designers should examine the ways in which they work together and take into consideration the impact this has on the delivery of the educational experience.